Immune priming prior to pathogen exposure sheds light on the relationship between host, microbiome and pathogen in disease. Issue 2 (1st February 2023) - Kaganer, Alyssa W.; Ossiboff, Robert J.; Keith, Nicole I.; Schuler, Krysten L.; Comizzoli, Pierre; Hare, Matthew P.; Fleischer, Robert C.; Gratwicke, Brian; Bunting, Elizabeth M.
Abstract : Dynamic interactions between host, pathogen and host-associated microbiome dictate infection outcomes. Pathogens including Batrachochytrium dendrobatidis (Bd) threaten global biodiversity, but conservation efforts are hindered by limited understanding of amphibian host, Bd and microbiome interactions. We conducted a vaccination and infection experiment using Eastern hellbender salamanders ( Cryptobranchus alleganiensis alleganiensis ) challenged with Bd to observe infection, skin microbial communities and gene expression of host skin, pathogen and microbiome throughout the experiment. Most animals survived high Bd loads regardless of their vaccination status and vaccination did not affect pathogen load, but host gene expression differed based on vaccination. Oral vaccination (exposure to killed Bd) stimulated immune gene upregulation while topically and sham-vaccinated animals did not significantly upregulate immune genes. In early infection, topically vaccinated animals upregulated immune genes but orally and sham-vaccinated animals downregulated immune genes. Bd increased pathogenicity-associated gene expression in late infection when Bd loads were highest. The microbiome was altered by Bd, but there was no correlation between anti-Bd microbe abundance or richness and pathogen burden. Our observations suggest that hellbenders initially generate a vigorous immune response to Bd, which is ineffective at controlling disease and is subsequently modulated. Interactions with antifungal skin microbiota did not influence disease progression.